Pre –treatment implant CBCT Analysis of Anterior Mental Loop Length, Lingual Concavity and Inclination of Alveolar Ridge in the Mandible – A UAE Study - Asok Mathew1 , Raghad Mohammed Sadiq2 , Suleiman Ergieg3 , Maher al Shayeb4 , Eyas Abuhijleh5 , Sudh (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aims: This study aims to use 3D imaging (CBCT) in order to identify the presence of anterior mental loop,know its dimensions and variation in anatomy, lingual concavity and the angle of tilt in the mandibular ridgeaiding in better treatment planning for surgical approaches.Method: Forty CBCT images of patients scanned by Planmeca Romexis for different diagnostic purposes,were analyzed using the Romexis software.Results: The study results showed that mental loop was present in 62.5% of patients on the right side and 70%of patients on the left side, with a mean length ranging from 0.30 mm to 3.12 mm. The presence of anteriorcanal was observed in 5 patients (2 Females and 3 Males) 12.5% of the cases examined. As mentioned inmethodology lingual concavity was classified based on its morphology into three classifications: A (Acuteundercut) B (stream line) C (Kidney shape), with class C (Kidney shape) amounting up to 42.5% of the caseswhile the least common was class B (stream line). In 40% of the cases, deepest lingual concavity was in theregion of the second molar.Conclusions: Placement of implants in the molar region of the mandible may result in perforation of thelingual cortex due to severely inclined ridge or deep lingual concavity. Presence of mental loop and anteriormandibular canal in the region of mandibular region needs careful evaluation using different tomographicslices.